B-Cell Activating Factor Profile and Quality of Life in Systemic LupusErythematosus Patients - Laniyati Hamijoyo (Indonesian Journal of Rheumatology, 2022)
Background: B-Cell Activating Factor (BAFF) is a cytokine that plays a rolein systemic lupus erythematosus (SLE) pathogenesis.  BAFF increases B cellfunction, which will affect disease activity.  In addition to decreasing diseaseactivity, good quality of life (QoL) is one of the goals to be achieved in SLEtherapy, which is also affected by disease activity.  The purpose of this studyis to know the correlation of the BAFF profile with the QoL of SLE patients.Methods:  This was a cross-sectional study using secondary data from aprevious study.  The subjects of this study were SLE patients who had visitedthe rheumatology outpatient clinic or were hospitalized in Hasan SadikinHospital Bandung from September 2016 until February 2017.  Subjects wereasked to complete the Short Form-36 and measure their BAFF level inserum.  Demographic data were collected, and disease activity data wereassessed by Mexican Systemic Lupus Erythematosus Disease Activity Index(MEX-SLEDAI).  The statistical analysis used in this study was the Spearmantest. Results: There was a positive correlation between BAFF and MEXSLEDAI (r 0.238, p-value 0.038).  There was also a negative correlationbetween MEX-SLEDAI and PCS, as well as the MCS score (r -0.392 and 0.371, p-value <0.05). Conclusion:  BAFF levels will increase in higherdisease activity which will affect a poorer quality of life.